AKTUALISASI TRADISI MEBUUG-BUUGAN SEBAGAI BENTENG BUDAYA DI DESA ADAT KEDONGANAN, KECAMATAN KUTA, KABUPATEN BADUNG - I Made Sudarsana; Ida Ayu Gede Prayitna Dewi (UNHI PRESS, 2019)
The existence of traditional arts, has now become an image of regional culture and is able to have a dynamic impact on the community. The tradition that develops, and is grounded in an area certainly through a long journey process so that it becomes a system of habits that is carried out continuously. The formation of a similar perspective and associated with local mythology, is the initial foundation for an initiator and local genius to formulate his perspective in the traditional space. This shows that the role of tradition today, can be used as a barometer of wealth that has high investment in an area. The phenomenon of the emergence of tradition that has been marginalized for its existence, nowadays it is as if it will become a gem of high value and the emergence of the reconstruction of lost traditions. Particularly in the Adong Village of Kedonganan, Kuta District of Badung Regency, the Mebuug - buugan tradition has been reconstructed since 2014 ago. This tradition, which is left behind almost 60 years, is a game tradition using mud / buug in mangroves. The continuity of this tradition is able to elevate the local wisdom contained in it, especially in the Traditional Village of Kedonganan. Many philosophical contents and social values ​​can be implemented through this Mebuug buugan traditional media. The application of the Tri Hita Karana concept in the Mebuug Buugan tradition is very relevant to the efforts of the community to maintain a harmonious relationship or social interaction of the people and the ecology of the natural environment of the Mangrove.